The role of social support and spiritual well-being on future anxiety among final year students - Azzahra Meita Syamsyiah Putri; Ratna Duhita Pramintari; Aldila Putri Anwa (Institute for Advanced Science, Social, and Sustainable Future, 2026)
Background: Students in their final year usually experience developments marked by various academic and social demands, such as writing a thesis, final exams, and preparing to enter the workforce. Social support and spiritual well-being are considered to play an important role in helping individuals cope with these pressures. Methods: This study aims to conduct an in-depth analysis of the role of social support on spiritual well-being on future anxiety among students who are in their final year. This study uses quantitative research methods. The number of participants involved was 60 participants from the Psychology study program at Universitas Islam “45” The instruments used included the Multidimensional Scale of Perceived Social Support, the Spiritual Well-Being Scale, and the Future Anxiety Scale. Data analysis was performed using Spearman's rho correlation test and multiple regression. Findings: The analysis findings show that social support and spiritual well-being together do not have a significant effect on future anxiety with a value of R = 0.201, R² = 0.041, and a significance level of 0.307. Conclusion: This means that these two variables only explain 4.1% of the variation in future anxiety, while 95.9% is influenced by other factors such as self-efficacy, life experiences, economic conditions, and individual coping strategies. Although the results are not statistically significant, this information highlights that social support and spiritual well-being play an important conceptual role in maintaining the psychological balance of students as they go through the transition phase to adulthood. Novelty/Originality of this article: The innovation of this study lies in the simultaneous analysis of social and spiritual dimensions on future anxiety in the context of final-year students at Islamic universities, which has been minimally researched empirically in Indonesia and provides a basis for the development of psychological interventions based on social and spiritual aspects to support student well-being.